The Role of Scientists in the Professional Development of Science Teachers - National Research Council (The National Academies Press, 1996)
Scientists nationwide are showing greater interest in contributing to the reform of science education, yet many do not know how to begin. This highly readable book serves as a guide for those scientists interested in working on the professional development of K-12 science teachers. Based on information from over 180 professional development programs for science teachers, the volume addresses what kinds of activities work and why. Included are useful examples of programs focusing on issues of content and process in science teaching. The authors present "day-in-a-life" vignettes, along with a suggested reading list, to help familiarize scientists with the professional lives of K-12 science teachers. The book also offers scientists suggestions on how to take first steps toward involvement, how to identify programs that have been determined effective by teachers, and how to become involved in system-wide programs. Discussions on ways of working with teachers on program design, program evaluation, and funding sources are included. Accessible and practical, this book will be a welcome resource for university, institutional, and corporate scientists; teachers; teacher educators; organizations; administrators; and parents.
Keywords: Education

Resources for Teaching Elementary School Science (The National Academies Press, 1996)
What activities might a teacher use to help children explore the life cycle of butterflies? What does a science teacher need to conduct a "leaf safari" for students? Where can children safely enjoy hands-on experience with life in an estuary? Selecting resources to teach elementary school science can be confusing and difficult, but few decisions have greater impact on the effectiveness of science teaching. Educators will find a wealth of information and expert guidance to meet this need in Resources for Teaching Elementary School Science. A completely revised edition of the best-selling resource guide Science for Children: Resources for Teachers, this new book is an annotated guide to hands-on, inquiry-centered curriculum materials and sources of help in teaching science from kindergarten through sixth grade. (Companion volumes for middle and high school are planned.) The guide annotates about 350 curriculum packages, describing the activities involved and what students learn. Each annotation lists recommended grade levels, accompanying materials and kits or suggested equipment, and ordering information. These 400 entries were reviewed by both educators and scientists to ensure that they are accurate and current and offer students the opportunity to: Ask questions and find their own answers. Experiment productively. Develop patience, persistence, and confidence in their own ability to solve real problems. The entries in the curriculum section are grouped by scientific area—Life Science, Earth Science, Physical Science, and Multidisciplinary and Applied Science—and by type—core materials, supplementary materials, and science activity books. Additionally, a section of references for teachers provides annotated listings of books about science and teaching, directories and guides to science trade books, and magazines that will help teachers enhance their students' science education. Resources for Teaching Elementary School Science also lists by region and state about 600 science centers, museums, and zoos where teachers can take students for interactive science experiences. Annotations highlight almost 300 facilities that make significant efforts to help teachers. Another section describes more than 100 organizations from which teachers can obtain more resources. And a section on publishers and suppliers give names and addresses of sources for materials. The guide will be invaluable to teachers, principals, administrators, teacher trainers, science curriculum specialists, and advocates of hands-on science teaching, and it will be of interest to parent-teacher organizations and parents.
Keywords: Education

National Science Education Standards - National Research Council (The National Academies Press, 1996)
Americans agree that our students urgently need better science education. But what should they be expected to know and be able to do? Can the same expectations be applied across our diverse society? These and other fundamental issues are addressed in National Science Education Standards—a landmark development effort that reflects the contributions of thousands of teachers, scientists, science educators, and other experts across the country. The National Science Education Standards offer a coherent vision of what it means to be scientifically literate, describing what all students regardless of background or circumstance should understand and be able to do at different grade levels in various science categories. The standards address: The exemplary practice of science teaching that provides students with experiences that enable them to achieve scientific literacy. Criteria for assessing and analyzing students' attainments in science and the learning opportunities that school science programs afford. The nature and design of the school and district science program. The support and resources needed for students to learn science. These standards reflect the principles that learning science is an inquiry-based process, that science in schools should reflect the intellectual traditions of contemporary science, and that all Americans have a role in improving science education. This document will be invaluable to education policymakers, school system administrators, teacher educators, individual teachers, and concerned parents.
Keywords: Education